The politics of environment ; Population story [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Residence of Apalit, Pampanga are complaining about polluted water that destroys their environment ; Looks into the government;s priorities in relation to a growing population.
The Politics of environment (14 min.) -- Population story (21 min.)
VHS.
Keywords: Central Fermentation Industrial Corporation; Pollution -- Environmental aspects -- Philippines; Pollution -- Government policy. -- Philippines; Population -- Government policy. -- Philippines